(untitled) (Nigerian Journal of Technology, 2015)
This paper describes the analysis of the Homomorphic filtering algorithm, the equivalency between the frequency and spatial-domain methods and the implementation of low-pass and high-pass spatial domain Homomorphic filter in low power embedded devices. It is shown that the Homomorphic filter in the spatial domain combines the sensitivity of local/neighbourhood operations in addition to Laplacian-type edge enhancement, averaging operation of illumination intensity estimation, in addition to dynamic range compression associated with frequency-domain Homomorphic filters. A qualitative and quantitative comparison of the image results confirms the validity of the theoretical approach and advantages for digital hardware implementation. The developed filters are implemented on a Java-enabled mobile phone and form a low cost embedded image processing enhancement system. http://dx.doi.org/10.4314/njt.v34i2.19